2015
DOI: 10.1007/s00253-015-6555-8
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane proteins related to SusC and SusD are not required for Cytophaga hutchinsonii cellulose utilization

Abstract: Cytophaga hutchinsonii, a member of the phylum Bacteroidetes, employs a novel collection of cell-associated proteins to digest crystalline cellulose. Other Bacteroidetes rely on cell surface proteins related to the starch utilization system (Sus) proteins SusC and SusD to bind oligosaccharides and import them across the outer membrane for further digestion. These bacteria typically produce dozens of SusC-like porins and SusD-like oligosaccharide-binding proteins to facilitate utilization of diverse polysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…C. hutchinsonii does not appear to use this system to utilize cellulose. It has two susClike genes and two susD-like genes, but the deletion of all of these resulted in no defect in cellulose utilization (27). C. hutchinsonii may have a novel mechanism to transport cellodextrins into the periplasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. hutchinsonii does not appear to use this system to utilize cellulose. It has two susClike genes and two susD-like genes, but the deletion of all of these resulted in no defect in cellulose utilization (27). C. hutchinsonii may have a novel mechanism to transport cellodextrins into the periplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial adhesion to cellulose was measured, as previously described (27), by mixing cells with Avicel PH-101, sedimenting the cellulose particles and attached bacteria by centrifugation at 100 ϫ g for 1 min, and measuring the optical density of the supernatants (see Supplemental Methods in the supplemental material for details).…”
Section: Methodsmentioning
confidence: 99%
“…A cellulose binding experiment was carried out as described by Zhu et al (45). Protein was incubated with 10% (wt/vol) Avicel (or 1% [wt/vol] RAC) in a final volume of 400 l that contained 1 mg/ml protein and 5% Avicel (or 0.5% RAC).…”
Section: Primermentioning
confidence: 99%
“…C. hutchinsonii has two susC-like genes and two susD-like genes (3). Recent results, however, have revealed that the susC-like and susD-like genes are not required for efficient cellulose utilization or for growth of C. hutchinsonii on crystalline cellulose (17), indicating that the Bacteroidetes Sus paradigm for polysaccharide utilization may not apply to C. hutchinsonii cellulose utilization. C. hutchinsonii may thus adopt an alternative mode of utilization in which the cell surface enzymes of C. hutchinsonii digest cellulose extracellularly to cellobiose and glucose, eliminating the need for SusC-like and SusD-like proteins to import longer oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…For C. hutchinsonii, previous results indicated that, besides cellulose, glucose and cellooligosaccharides can also be rapidly assimilated, and such reducing sugars do not accumulate in the culture supernatant when C. hutchinsonii is cultivated with cellulose as the sole carbon source (4,7). Although two susC-like genes, each arranged in tandem with a susD-like gene, could be identified in the C. hutchinsonii genome, functional characterization revealed that the two sus-like pairs are not required for C. hutchinsonii cellulose utilization (17).…”
mentioning
confidence: 99%